PENGARUH KUALITAS PELAYANAN, SANKSI, SIKAP FISKUS, KEMANFAATAN NPWP, DAN SOSIALISASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI PENGUSAHA - Tri Wahyuningsih, Rispantyo & Dewi Saptantinah Puji Astuti (Universitas Slamet Riyadi, 2019)
The objective of research was to analyze the significant effect of taxing service quality, taxing sanction, tax officer’s attitude, taxpayer registration number’s usefulness, and taxing socialization on taxpayers’ compliance. This research employed a case study conducted among employer taxpayers enlisted in KPP Pratama Sukoharjo. Data source consisted of primary and secondary ones. Meanwhile, technique of collecting data used was questionnaire. The sample of research consisted of 51 respondents taken using incidental sampling technique. Techniques of analyzing data used were validity, reliability, classical assumption, and hypothesis tests. The result of research showed that partially there was no significant effect of taxing service quality, taxing sanction, tax officer’s attitude, taxpayer registration number’s usefulness, and taxing socialization on taxpayers’ compliance. Meanwhile, simultaneously there was a significant effect of taxing service quality, taxing sanction, tax officer’s attitude, taxpayer registration number’s usefulness, and taxing socialization on taxpayers’ compliance. Keywords: taxing service quality, taxing sanction, tax officer’s attitude, taxpayer registration number’s usefulness, taxing socialization, taxpayers’ compliance